Gender Differences in Relationship Maintenance Behaviors and Relationship Satisfaction - Legkauskas, Visvaldas; Pazniokaitė, Gintarė (Social Welfare: Interdisciplinary Approach, 2018)
The present study investigated whether there are gender differences in how perceived use of relationship maintenance strategies by a partner is linked to subject’s relationship satisfaction in a Lithuanian sample. The sample consisted of 472 participants in committed romantic relationship, including 389 women and 83 men with a mean age of 21.89 years. The sample included 232 participants in dating relationship, 216 cohabiting and 24 married. Mean relationship duration was 31.91 months. Stafford’s (2011) Relationship Maintenance Behaviors Measure was used to assess relationship maintenance, while relationship satisfaction was measured by Couples Satisfaction Index (CSI-32) of Funk and Rogge (2007). Results of the study indicated that women perceived their partners using more positivity, understanding, assurances, sharing tasks, and social network strategies than men did. While no statistically significant gender differences in relationship satisfaction were found, all relationship maintenance strategies were positively correlated with relationship satisfaction for both men and women. However, strategies contributing towards prediction of relationship satisfaction differed for men and women. For women, relationship satisfaction was best predicted by perceived assurances, followed by understanding, positivity, and self-disclosure, which collectively accounted for just under 40% of variance in relationship satisfaction. For men, only perceived partner’s positivity was significant predictor of relationship satisfaction, but it alone accounted for 51.6 percent of variance in relationship satisfaction. Neither relationship status nor relationship duration were significant in predicting relationship satisfaction of either men or women.